Pre-transplant gene profiling characterization by next-generation DNA sequencing might predict relapse occurrence after hematopoietic stem cell transplantation in patients affected by AML - Metafuni, Elisabetta; Amato, Viviana; Giammarco, Sabrina; Bellesi, Silvia; Rossi, Monica; Minnella, Gessica; Frioni, Filippo; Limongiello, Maria Assunta; Pagano, Livio; Bacigalupo, Andrea; Sica, Simona; Chiusolo, Patrizia (Frontiers in Oncology, 2022)
Background: In the last decade many step forward have been made in acute myeloid leukemia prognostic stratification adding next generation sequencing techniques to the conventional molecular assays. This resulted in revision of current risk classification and introduction of new target therapy. Aims and methods: we wanted to evaluate the prognostic impact of AML mutational pattern on relapse occurrence and survival after allogeneic stem cell transplantation. A specific NGS panel containing 26 genes was designed for the study. Ninety-six patients studied with NGS before transplantation were included and retrospectively studied for post-transplant outcomes. Results: only 8 patients did not show any mutations. Multivariate Cox regression revealed FLT3 (HR 3.36, p=0.02), NRAS (HR 4.78, p=0.01), TP53 (HR 4.34, p=0.03) and WT1 (HR 5.97, p=0.005) mutations as predictive variables for relapse occurrence after transplantation. Other independent variables for relapse recurrence were donor age (HR 0.97, p=0.04), the presence of an adverse cytogenetic risk at diagnosis (HR 3.03, p=0.04) and the obtainment of a complete remission of the disease before transplantation (HR 0.23, p=0.001). Overall survival appeared to be affected only by grade 2-4 acute GvHD occurrence (HR 2.29, p=0.05) and relapse occurrence (HR 4.33, p=0.0001) in multivariate analysis. Conclusions: the small number of patients and the retrospective design of the study might affect the resonance of our data. However, although results on TP53, FLT3 and WT1 were comparable to previous reports, the interesting data on NRAS deserves attention.